Issues in Islamic hedging practices: a critical analysis - Kasri, Noor Suhaida; Abdul Rahman, Zaharuddin; Mohamad, Shamsiah; Habib, Farrukh (ISRA Publication, 2016)
Hedging is an important concept in overall risk management in conventional finance. The need for hedging is also recognised in Islamic finance, although hedging strategies in Islamic finance are different from their conventional counterparts as they must be in compliance with the Sharīʿah principles. Accordingly, the following international Sharīʿah standard-setting bodies and other Sharīʿah authorities outside Malaysia have issued resolutions acknowledging the need for hedging and discussing various instruments to be used for that purpose: • the Islamic Fiqh Academy of the Organisation of Islamic Cooperation (IFA-OIC); • the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI); • the International Islamic Financial Market (IIFM); • Dallah al-Baraka (DAB); • National Sharia Board-Indonesian Council of Ulama (DSNMUI). The following local Sharīʿah standard-setting bodies have also issued relevant resolutions: • the Shariah Advisory Council of Bank Negara Malaysia (SACBNM); • the Shariah Advisory Council of Securities Commission Malaysia (SAC-SC).A careful examination of these resolutions reveals that the hedging approved for use in Islamic finance is distinct from hedging in conventional finance. The distinction lies in four major factors: (i) the hedging contract and its underlying assets must be Sharīʿah compliant; (ii) the use of the hedging mechanism is not to be for speculation and gambling; (iii) the hedging transaction is to be carried out based on actual underlying risk arising from an investment which adds value to the real economy; and (iv) the strategy or technique involved in hedging risk does not sever the risk from its underlying assets. Though the Sharīʿah advisory bodies mentioned above are in agreement on the need for hedging, they are not unanimous on the legality of the prevalent hedging products. This research focuses on the resolutions of the SAC-BNM and the SAC-SC that approve hedging products—for instance, forwards, futures, swaps and options—as Sharīʿah compliant. Despite the fact that such products are resolved to be Sharīʿah compliant by the SAC-SC and SAC-BNM, the practice on the ground seems to show otherwise.